Synchronous hybrid procedure combining interventional radiology and endoscopy for esophagogastric varices with large gastro-renal shunt. Issue 17 (April 2020) - Zhao, Yiming; Wang, Shufang; Li, Congyong; Guo, Liangliang; Li, Chao; Zhao, Li; Tian, Le; Zheng, Siyang; Liu, Jiangtao; Sun, Gang
Abstract : Abstract: Successful treatment of esophagogastric varices (EGV) with giant portal-systemic shunt is challenging. To explore the feasibility and safety of a novel hybrid procedure involving interventional radiology and endoscopy in the same sitting. Three cases clinically diagnosed to have decompensated cirrhosis and EGV with giant gastrorenal shunt (GRS) on contrast-enhanced computed tomography (CT) were included. The hybrid procedures included: indirect portography, hepatic vein pressure gradient (HVPG) measurement, HVPG-based partial splenic embolization (PSE), retrospective GRS balloon occlusion, endoscopic histoacryl injection (EHI), balloon catheter radiography and withdrawal. All the procedures were done in the same operation room. Main outcomes measurements included operation time, complications, and re-bleeding events. Hybrid interventions were performed successfully in 3 cases with a mean operation time of 63.3 minutes without any major intra- and post-operation complications. No rebleeding occurred at 6-month follow-up. Synchronous hybrid intervention combining radiology and endoscopy is feasible and safe for patients with EGV and giant GRS, preliminary study with limited cases deserves further exploration.